Properties of polymers : their correlation with chemical structure ; their numerical estimation and prediction from additive group contributions - Krevelen, D. W. van (Elsevier, 2009)
This authoritative, widely cited book has been used all over the world. The fourth edition incorporates the latest developments in the field while maintaining the core objectives of previous editions: to correlate properties with chemical structure and to describe methods that permit the estimation and prediction of numerical properties from chemical structure, i.e. nearly all properties of the solid, liquid, and dissolved states of polymers. * extends coverage of critical topics such as electrical and magnetic properties, rheological properties of polymer melts, and environmental behavior and failure * discusses liquid crystalline polymers across chapters 6, 15, and 16 for greater breadth and depth of coverage * increases the number of supporting illustrations from approximately 250 (in the previous edition) to more than 400 to further aid in visual understanding.